ANALISIS PENERIMAAN PAJAK REKLAME DI KOTA SEMARANG TAHUN 1990-2011 - Gupita P, Lintan; SBM, Nugroho (Diponegoro Journal of Economics, 2013)
The purpose of this study was to analyze the influence of the number of Inhabitants, the number of industry, and the per capita gross Regional domestic product Advertisement tax revenue as well as to find out how big the Tax Elasticity, the effectiveness of Billboard Billboard Advertisement, the proportion of the tax, and the Tax Revenue against Billboard Correlation Region in the city of Semarang.Statistical testing using multiple linear regression (Multiple Linear Regression Method) with least squares method or Ordinary Least Square (OLS). Testing the elasticity of Tax Elasticity Analysis by Billboard, Advertisement Tax Effectiveness with the analysis of the effectiveness, the proportion of Tax Analysis with Billboard proportions, and for testing the correlation of Advertisement Tax through a t-test.Test results simultaneously indicates that GDP, the number of industry and population simultaneously affect tax revenue Billboard in the city of Semarang. Regression analysis showed that the population of tax effect on Billboard, while other free variables such as number of industry and GDP per capita has no effect and is not significant to the growth of Tax Billboard in the city of Semarang and the results of other analyses such as Elasticity, the effectiveness, the proportion and the correlation of the Advertisement Tax has very close relationship on a PAD, so that if a Billboard Tax rises then the PAD also rose, by contrast Tax Billboard down then the PAD will also go down.